Prevention of early sudden cardiac death after myocardial infarction using the wearable cardioverter defibrillator - results from a real-life cohort. (19th May 2022) - Rohrer, U; Manninger, M; Odeneg, T; Ebner, C; Moertl, D; Keller, H; Dirninger, A; Stix, G; Alber, H; Steinwender, C; Binder, R; Stuehlinger, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Patients are at elevated risk of sudden cardiac death (SCD) after acute myocardial infarction (MI). The VEST trial failed to show a significant reduction in arrhythmic mortality in patients prescribed with a wearable converter-defibrillator (WCD), having a lower than expected wearing compliance. We aimed to investigate the incidence of WCD treatments and outcomes of all patients with acute MI and LVEF ≤35% in a real life and well-compliant cohort in Austria. Methods: We performed a retrospective analysis of all patients meeting the in- and exclusion criteria of the original VEST trial within the Austrian WCD registry between 2010 and 2021. Results: 105/896 patients (12%) with an average age of 64±11 years (12% female; LVEF 28±6%) registered in the Austrian WCD registry met the VEST in- and exclusion criteria. 104/105 patients were revascularized and prescribed with a WCD prescription for 69 (1;277) days, the median wearing duration was 23.5 (0;24) hours/day. 4/105 (3.8%) patients received 9 appropriate WCD shocks, the per patient shock rate was 2 (1;5). No inappropriate shock was delivered. During follow-up, 46/105 patients (44%) received an ICD after the WCD period, 4/105 (3.8%) patients died during follow-up. Arrhythmic mortality (1.9% Austria vs. 1.6% VEST, p=ns), as well as all-cause mortality (3.8% vs. 3.1%, p=ns) in the Austrian cohort were comparable to the VEST cohort. Conclusion: The WCD is a safe treatment option in a highly selected cohort of patients with a LVEF ≤35% after acute myocardial infarction. However, despite excellent WCD compliance as opposed to the VEST study, only 3.8% of patients receive appropriate WCD shocks and the arrhythmic mortality rate was not significantly improved.